The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijerph17176258
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Tooth Loss in Patients Undergoing Mid-Long-Term Maintenance: A Retrospective Study

Abstract: In this retrospective study, we identified risk factors for tooth loss in patients undergoing mid–long-term maintenance therapy. We surveyed 674 maintenance patients for ≥5 years after active treatment who visited a dental clinic between January 2015 and December 2016. Of these, 265 were men (mean age 54.6 ± 8.0 years old) and 409 were women (mean age 54.0 ± 7.9 years old). Study variables included patient compliance, sex, number of teeth lost, cause of tooth loss (dental caries, periodontal disease, root frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 37 publications
(7 reference statements)
2
12
0
Order By: Relevance
“…Age and sex were not correlated with tooth loss (p = 0.81, p = 0.10, respectively). The other results regarding the role of compliance, general health status, smoking, and periodontal bone loss, already presented and discussed in our previous study [15], were also confirmed for this cohort. Briefly, most lost teeth were non-vital teeth and the most common cause of tooth loss was tooth fracture.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Age and sex were not correlated with tooth loss (p = 0.81, p = 0.10, respectively). The other results regarding the role of compliance, general health status, smoking, and periodontal bone loss, already presented and discussed in our previous study [15], were also confirmed for this cohort. Briefly, most lost teeth were non-vital teeth and the most common cause of tooth loss was tooth fracture.…”
Section: Discussionsupporting
confidence: 88%
“…Other causes have been described in detail in a previous paper. [15] characteristic study variables and association with tooth loss are shown in Table 6. Logistic regression analysis was carried out for each variable.…”
Section: Outcome Datamentioning
confidence: 99%
“…Similar to the findings in men, the risk of tooth loss increases with age in women [35,40]. In women, the number of untreated teeth tended to be significantly higher in the Low group.…”
Section: Discussionsupporting
confidence: 82%
“…This finding was also reported in previous studies. 15–17 These studies rationalized the higher number of tooth extraction among males due to less interest in adhering to dental maintenance and recall programs plus common smoking habits among males.…”
Section: Discussionmentioning
confidence: 99%
“… 8 On the other hand, Kawahara et al have reported that there was no clear correlation between systemic diseases, such as diabetes, and tooth loss. 15 …”
Section: Discussionmentioning
confidence: 99%